2016
DOI: 10.1038/srep32525
|View full text |Cite
|
Sign up to set email alerts
|

Projected loss of soil organic carbon in temperate agricultural soils in the 21st century: effects of climate change and carbon input trends

Abstract: Climate change and stagnating crop yields may cause a decline of SOC stocks in agricultural soils leading to considerable CO2 emissions and reduced agricultural productivity. Regional model-based SOC projections are needed to evaluate these potential risks. In this study, we simulated the future SOC development in cropland and grassland soils of Bavaria in the 21st century. Soils from 51 study sites representing the most important soil classes of Central Europe were fractionated and derived SOC pools were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
56
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(76 citation statements)
references
References 88 publications
2
56
1
2
Order By: Relevance
“…Our results agree with other studies that examine changes in soil C stocks as they respond to climate change, despite some potential methodological limitations (Meersmans et al, 2016; Wiesmeier et al, 2016). While our study focused on topsoil C stocks, recent evidence suggests that potential C losses in topsoil may be somewhat offset by gains in deeper soil layers (Muñoz‐Rojas et al, 2017).…”
Section: Resultssupporting
confidence: 91%
“…Our results agree with other studies that examine changes in soil C stocks as they respond to climate change, despite some potential methodological limitations (Meersmans et al, 2016; Wiesmeier et al, 2016). While our study focused on topsoil C stocks, recent evidence suggests that potential C losses in topsoil may be somewhat offset by gains in deeper soil layers (Muñoz‐Rojas et al, 2017).…”
Section: Resultssupporting
confidence: 91%
“…Another soil organic C physical fractionation scheme has been proposed to initialize the rothC model (Zimmermann et al, 2006;Wiesmeier et al, 2016;Nemo et al, 2017) Thermal analysis provides reliable and cost-effective information on the biogeochemical stability of soil C and can be used to estimate the size of soil organic C fractions (Saenger et al, 2015;Barré et al, 2016;Campo and Merino, 2016) Standards for measurement and calculation of proxies of soil contribution to GHGs emissions and C storage…”
Section: Resultsmentioning
confidence: 99%
“…For example, the YASSO model describes different kinetic pools for litter and SOC, which are determined by chemical extractions in water, ethanol and acid (Tuomi et al, 2011). The size of the soil C pools of the rothC model can also be initialized by a SOC physical fractionation scheme (Zimmermann et al, 2006;Wiesmeier et al, 2016;Nemo et al, 2017). The NoE algorithm (Hénault et al, 2005), which is used to simulate N 2 O emissions in various agroecosystem models, explicitly integrates the soil capacity to reduce N 2 O (Hénault et al, 2001).…”
Section: Needed Standards According To Policy Requirementsmentioning
confidence: 99%
“…The distribution of residue C in different SOM pools (i.e., labile and recalcitrant C pools) can greatly modify SOC accumulation and stabilization (Majumder and Kuzyakov, 2010; Qiao et al, 2014) due to the contrasting turnover rate of the fast and slow C pools. However, it is also commonly observed that long‐term residue return did not increase SOC stocks (e.g., Fontaine et al, 2004; Wiesmeier et al, 2016), highlighting the importance of other soil factors, such as microbial activity and nitrogen (N) availability, in the preservation of residue‐derived C and SOC dynamics (Zhang et al, 2014).…”
mentioning
confidence: 99%
“…not increase SOC stocks (e.g., Fontaine et al, 2004;Wiesmeier et al, 2016), highlighting the importance of other soil factors, such as microbial activity and nitrogen (N) availability, in the preservation of residue-derived C and SOC dynamics (Zhang et al, 2014).…”
mentioning
confidence: 99%